How deep is the soil? / Ahmed Azhar Jaafar - Jaafar, Ahmed Azhar (2003)
Biologic processes are studied to prove the claim that soil is much deeper than the depths mentioned in textbooks. These processes involve the spatial and temporal patterns of carbon dioxide in soil air, carbonic acid in soil solution and soil-exchangeable acidity. The lower boundary of soil is difficult to determine precisely, however with the inclusion of C-horizon parent material, the lower limit of soil could be tens of meters deep.